The Effect of Unexpected Chart Positions on the Firm Value of Music Labels. An Event Study of Album Success - Nima Mehrafshan; Björn Goerke; Michel Clement (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We conduct an event study to (1) analyze whether investors revise their expectations about a music album's success when new chart information is published and (2) estimate how these revised expectations affect the value of a music label. We find that expectations about the success of an album are formed with respect to the performance of the promotional singles and that failure to meet these expectations leads to negative stock returns. However, unexpectedly high chart positions do not lead to significantly higher valuations of labels. The initial album success is anticipated at a very early stage when single charts are released one week prior to the release of the initial album charts.
Additional information: Eine vorherige Version wurde im Rahmen einer anderen kumulativen Dissertation bereits wie folgt veröffentlicht: Mehrafshan, N. (2013). Essays on Value Creation in Marketing Management. Unveröffentlichte Dissertation. Universität Hamburg.
Keywords: M31; O3; 330; Event Study Methodology; Product Samples; Music industry; expectation model